Self-Efficiency and Student Learning Motivation in Increasing Arabic Language Master: (Case study in STAI Syaichona Moh. Cholil Bangkalan) - Mutmainah Mutmainah (Qismul Arab: Journal of Arabic Education, 2021)
Self-efficacy and student learning motivation are important in improving Arabic mastery at STAI Syaichona Moh. Choli Bangkalan. This study aims firstly to identify students' self-efficacy and learning motivation in improving Arabic mastery at STAIS, secondly to identify factors that influence student self-efficacy and learning motivation in improving Arabic mastery at STAIS. This research is a qualitative research with a phenomenological approach. The data collection technique used in-depth interviews, observation, and documentation. The validity of the data using triangulation of sources and methods. The results of the study are first, self-efficacy and learning motivation are able to increase mastery of Arabic at STAIS, including; able to improve the ability of maharah al istima ', maharah al kalam, maharah al qira'ah, maharah al kitabah. Second, there are two factors that are self-efficacy of students in increasing mastery of Arabic at STAIS, namely internal factors, namely factors from within the students themselves. Internal factors include: individual perceptions of their own performance, status or individual roles in increasing self-confidence, student experiences, physiological and emotional states. External factors that affect student self-efficacy include: the nature of the task at hand, internal intensiveness, information, verbal persuasion. While learning motivation is influenced by internal factors including: physiological, and psychological. For external factors include: social and non-social.